2020
DOI: 10.1038/s41535-020-0240-6
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced superconductivity and topological phase transitions in the topological nodal-line semimetal SrAs3

Abstract: Topological nodal-line semimetals (TNLSMs) are materials whose conduction and valence bands cross each other, meeting a topologically protected closed loop rather than discrete points in the Brillouin zone (BZ). The anticipated properties for TNLSMs, include drumhead-like nearly flat surface states, unique Landau energy levels, special collective modes, long-range Coulomb interactions, or the possibility of realizing high-temperature superconductivity. Recently, SrAs 3 has been theoretically proposed and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Recently, there are a lot of topological materials that were experimentally and theoretically reported, [24] including the metal pnictides which have been reported to possess topological properties at ambient pressure and even under high pressure, such as TaAs 2 [25] and SrAs 3 . [16] Theoretically, CrP 4 was predicted to be a topological high-symmetry line semimetal when spinorbit coupling (SOC) was not considered very recently. [18] The electronic band calculations showed that CrP 4 is a semiconductor with an indirect bandgap of 0.47 eV according to the density functional theory calculation in the study by Khan et al [26] Instead, CrP 4 was reported to have a direct bandgap of 0.63 eV in Gong's research work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there are a lot of topological materials that were experimentally and theoretically reported, [24] including the metal pnictides which have been reported to possess topological properties at ambient pressure and even under high pressure, such as TaAs 2 [25] and SrAs 3 . [16] Theoretically, CrP 4 was predicted to be a topological high-symmetry line semimetal when spinorbit coupling (SOC) was not considered very recently. [18] The electronic band calculations showed that CrP 4 is a semiconductor with an indirect bandgap of 0.47 eV according to the density functional theory calculation in the study by Khan et al [26] Instead, CrP 4 was reported to have a direct bandgap of 0.63 eV in Gong's research work.…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, the atomic arrangements of the compounds containing light elements at higher pressures are those observed in analogous compounds with heavy elements of the same group at lower pressures, which is the so-called "corresponding static principle" rule such as Li 3 N (transforming from P6/mmm phase to P6 3 /mmc phase (which is the ambient pressure phase of Li 3 P) at 0.5 GPa, Fm-3m phase (which is the structure of Li 3 Bi at ambient pressure) at 36-45 GPa, [15] and SrAs 3 from C2/m phase to Pm-3m phase (the ambient pressure phase of SrBi 3 ) at 23.3 GPa. [16] Kinomura et al synthesized WP 4 using a cubic-type high-pressure vessel (3 GPa and 1000 C). The lattice parameters of WP 4 obtained by powder XRD were refined to obtain a body-centered tetragonal phase with a ¼ 5.702 Å and c ¼ 9.352 Å.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the non-magnetic CaP 3 family of materials was proposed as potential host of topological nodal-line (TNL) semimetals 6 , among which SrAs 3 possesses a TNL feature at ambient pressure 7 9 and exotic properties under high pressure 10 . Isostructural with SrAs 3 , EuAs 3 orders in an incommensurate antiferromagnetic (AFM) state at T N = 11 K, and then undergoes an incommensurate–commensurate lock-in phase transition at T L = 10.3 K, producing a collinear AFM ground state 11 – 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the NLSM superconductor has been studied intensively [9,10,[34][35][36][37][38][39][40][41][42][43][44][45]. In the superconducting state, the single-band inversion naturally becomes the double band inversion due to the particle-hole symmetry.…”
Section: Introductionmentioning
confidence: 99%